1989
DOI: 10.1089/dna.1.1989.8.1
|View full text |Cite
|
Sign up to set email alerts
|

The P450 Superfamily: Updated Listing of All Genes and Recommended Nomenclature for the Chromosomal Loci

Abstract: In this update we provide a list of the 71 P450 genes and the four P450 pseudogenes that have been characterized as of September 30, 1988. The chromosomal locations of many of these genes are also summarized. A modest revision of the initially proposed nomenclature of the P450 superfamily (Nebert et al., DNA 6, 1-11, 1987) is described specifically for the human and mouse chromosomal loci. The motivation for this revision is to conform to the rules of nomenclature for human and mouse genes. Recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
190
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 592 publications
(193 citation statements)
references
References 128 publications
3
190
0
Order By: Relevance
“…The cytochromes P450 are a multigene super-family of enzymes, existing as multiple forms, which metabolise a wide variety of xenobiotics and endogenous compounds including steroid hormones and arachidonic acid (Gonzalez, 1990;Nebert & Gonzalez, 1987;Nebert et al, 1989;Fitzpatrick & Murphy, 1988). This group of enzymes has a central role in activating and detoxifying chemical carcinogens and anticancer drugs (Guengerich, 1988).…”
mentioning
confidence: 99%
“…The cytochromes P450 are a multigene super-family of enzymes, existing as multiple forms, which metabolise a wide variety of xenobiotics and endogenous compounds including steroid hormones and arachidonic acid (Gonzalez, 1990;Nebert & Gonzalez, 1987;Nebert et al, 1989;Fitzpatrick & Murphy, 1988). This group of enzymes has a central role in activating and detoxifying chemical carcinogens and anticancer drugs (Guengerich, 1988).…”
mentioning
confidence: 99%
“…24,25 CY3A4 is the primary hepatic enzyme that metabolizes CsA, and it may contribute to a reduction in Effect of CY at conditioning on serum CsA levels serum CsA levels. 9,10 Longitudinal analysis showed that a significant difference of increment in serum CsA levels was observed at day 0 of HSCT. As autoinduction of CY generally begins within 24 h of CY administration, this rapid progression could explain the occurrence of this early significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…9,37 Metabolites of CsA are excreted into the bile. 10 Less than 1% of CsA is excreted in an unchanged form in urine. Another metabolic pathway involves P-glycoprotein, which is a membrane efflux pump that keeps intracellular drug concentrations low by transporting the drug out of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these substances are potent inducers of certain biotransformation reactions that are catalyzed by the cytochrome P-450-dependent monooxygenases, a super family of isozymic hemoproteins comprising more than 12 gene groups (8). These isozymes display broad substrate specificity and metabolize both endogenous substrates and xenobiotics to electrophilic derivatives, some of which can interact with DNA, thereby potentially activating protooncogenes or inactivating tumor suppressor genes.…”
mentioning
confidence: 99%